Exploring Greek-Cypriot media representations of national identities in ethnically divided Cyprus: the case of the 2002/2004 Annan Plan negotiations - Avraamidou, Maria (My University, 2018)
This paper explores Greek-Cypriot media representations of national identities during negotiations on a United Nation Plan (the Annan Plan), aiming to reunite ethnically divided Cyprus under a bi-zonal, bi-communal federation. The study analyzed thematically 57 editorials and lead commentaries published in all the daily Greek-Cypriot Press from the presentation of the Annan Plan in November 2002 to April 2004, at which point two simultaneous referenda were held. The study’s findings are consistent with ideas that national identifications are not static and provides an in-depth exploration of exclusive forms of Cypriot identities vis-à-vis more inclusive forms and vis-à-vis hellenocentric identifications.
Keywords: Conflict; Cyprus; Media; National identity; Nationalism